Sita Jaminan (Conservatoir Beslag) Menurut Herziene Indonesisch Reglement (HIR) Dalam Praktik Dikaitkan Dengan Kepastian Hukum dan Perlindungan Hukum - Agus Surachman (Jurnal Media Justitia Nusantara, 2017)
Not all Agreements will proceed according to what is promised, often we find that the agreement is not implemented or only partially done, and will make new legal problems, commonly called wanprestasi. Default means to break the promise (not keeping promises), or the absence of an achievement. The settlement of the default case can be done in 2 ways, ie through non-litigation (litigation) or litigation (legal process) process, the default lawsuit accompanied by the confiscation petition (conservatoir beslag) filed by the plaintiff to the Court is often not in accordance with what is expected by Plaintiffs because the rulings are less clear and the consequences of the judgment can not be executed (non-executable). Based on the above description, the author will write a scientific paper in the form of this thesis with the title: "Sita Jaminan (conservatoir beslag) According to Herziene Indonesisch Reglement (HIR) in Practice Associated With Legal Certainty and Legal Protection", the main issues that will be The study can be identified as follows: How does Sita Penjaminan (Conservatoir Beslag) in Practice be associated with Legal Certainty and Legal Protection? and How is the concept of Sita Penjaminan (Conservatoir Beslag) that is non-executable for the realization of Legal Certainty and Legal Protection? The research method used in this research is analytical descriptive method with normative juridical approach method. Data collection techniques used are document studies through library research to obtain secondary data, supported by interviewing through field research. The data analysis, is a juridical-qualitative analysis. Based on the results of research that has been done, the authors can take conclusions, namely as follows: Sita Collateral (Conservatoir Beslag) in practice associated with Legal Certainty and Legal Protection has not been fully implemented because of the often unclear verdict so that the confiscation of confiscation (conservatoir beslag) Petitioned by the plaintiff or creditor to be useless (illusoir), and as a result of his law the plaintiff has no legal protection and legal certainty. The concept of Sita Jaminan (Conservatoir Beslag) which is non-executive for the realization of Legal Certainty and Legal Protection is to be relevant between Posita Lawsuit, Petition Lawsuit, Legal Consideration in Decision and in Judgment of the panel of judges themselves, so Sita Jaminan (Conservatoir Beslag) will Is performed in accordance with the expectations of the Plaintiff and is justified by law in accordance with applicable legislation.